Finite element model and experimental verification of Glare laminate impact. Issue 1 (May 2020) - Cui, X; Zhang, Z Y; Wang, S
Abstract: In this paper, a finite element simulation model is established for the impact of Glare laminates, and the reliability of the model is verified by experiments. Glare applies the continuum damage mechanics (CDM) model and inputs the user material subroutine VUMAT to determine the damage of the material based on the theory of CDM under plane stress state. By comparing the ultrasonic scanning experiment after impact damage with the CDM finite element simulation cloud pattern used in this paper, the constitutive relation of the fibre continuous damage model used in this paper can better simulate the damage initiation, evolution and damage of internal materials.